Storytelling through Social Media - Brandon Telg; Jaron Jones; Ricky Telg; Becky Raulerson (EDIS)
You and your organization can use social media to tell your story and reach a large and diverse audience. This 3-page factsheet covers the major social media platforms, what each platform offers, and how to use theme effectively. Written by Brandon Telg, Jaron Jones, Ricky Telg, and Becky Raulerson, and published by the UF Department of Agricultural Education and Communication Department, July 2015.